Republic of Estonia : Staff Report for the 2009 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2010)
This 2009 Article IV Consultation highlights that the credit-fueled boom has resulted in a relatively large nonfinancial private sector debt stock in Estonia. With declining incomes, unemployment increasing sharply, and asset prices depressed, balance sheets of households and firms are under strain, weighing on domestic demand. Nonperforming loans have increased to more than 6 percent of total, and some banks are reporting losses. Executive Directors have supported the authorities' aim toward speedy adoption of the euro, noting its effects in fostering stability and confidence.